Prominent metallic surface conduction and the singular magnetic response of topological Dirac fermion in three-dimensional topological insulator Bi1.5Sb0.5Te1.7Se1.3 - Prithwish Dutta (Nature Portfolio, 2017)
Abstract We report semiconductor to metal-like crossover in the temperature dependence of resistivity (ρ) due to the switching of charge transport from bulk to surface channel in three-dimensional topological insulator Bi1.5Sb0.5Te1.7Se1.3. Unlike earlier studies, a much sharper drop in ρ(T) is observed below the crossover temperature due to the dominant surface conduction. Remarkably, the resistivity of the conducting surface channel follows a rarely observable T 2 dependence at low temperature, as predicted theoretically for a two-dimensional Fermi liquid system. The field dependence of magnetization shows a cusp-like paramagnetic peak in the susceptibility (χ) at zero field over the diamagnetic background. The peak is found to be robust against temperature and χ decays linearly with the field from its zero-field value. This unique behavior of the χ is associated with the spin-momentum locked topological surface state in Bi1.5Sb0.5Te1.7Se1.3. The reconstruction of the surface state with time is clearly reflected through the reduction of the peak height with the age of the sample.